DZIECIĘCA PROSTYTUCJA HOMOSEKSUALNA I PEDOFILIA - Lisiecki, Mirosław (Wydział Prawa i Administracji UAM, 1999)
The phenomenon of child’s prostitution and of the ensuing from it paedophilia increases constantly proportionally to deepening discordance between welfare and poverty and to still growing up moral relativism. Essential is also the question of emancipation of sexual behaviour recognized up to the present as being deviated (for instance: acceptance for official existence of gay’s organizations). The Author points out a series of problems which have an imminent link with certain part of the gay’s milieu; its member can - through a violence of legal rules, morals and morality - exert their criminogenic and wictimogenic influence on their social milieu. The Author, by the way of his considerations, devotes much place also to unlawful heterogenic contacts, to the phenomenon of sexually abused juveniles within their families and also - to juvenile prostitution and adequate means of preventing such a trade.
CHILD’S HOMOSEXUAL PROSTITUTION AND PAEDOPHILIA